A felőfokú végzettségű munkavállalók munkaerő-piaci helyzete és foglalkozásuk-iskolai végzettségük illeszkedse - Péter Galasi (Hungarian Academy of Sciences, Institute of Economics, 2008)
– The paper examines the labour-market position of persons with the higher-education diploma in Hungary. First, using simple labour-market indicators and international-comparison data, we find that persons with the higher-education diploma in Hungary are in a relatively good position in terms of both wage premium and unemployment. Second, analysing the occupation/education matching of workers having higher education diploma, we conclude that matching becomes better over time, and this is mainly due to a re-classification (upgrading) effect, that is, that more and more occupations are considered by the employers as occupations requiring higher-education diploma.
Keywords: J21; J23; J24; J31; 330; higher-education expansion; international comparison; occupation/education matching of workers with the higher education diploma; Akademiker; Hochqualifizierte Arbeitskräfte; Anforderungsprofil; Arbeitsmarkt; Ungarn